Teacher Competence in Developing Interactive Learning in Madrasah Ibtidaiyah in the 21st Century - Khairunisa, Destia; Aqida, Debby Silvia (Sunan Kalijaga International Journal on Islamic Educational Research, 2023)
The 21st century is known for its fast pace and is also recognized as the "knowledge age." In the process of learning, in the 21st century, students are required to achieve excellence and possess the 4C skills, which are Communication, Collaboration, Critical Thinking and problem solving, and innovative and creative. Certainly, in the application of these 4Cs, teachers need specific strategies and methods to ensure effective learning. There are four competencies that teachers must possess to carry out interactive learning in the classroom effectively. This research is conducted to analyze the competence of teachers in developing interactive learning in Islamic primary schools (Madrasah Ibtidaiyah) in the 21st century and to analyze the impact of interactive learning in Madrasah Ibtidaiyah in the 21st century. This research was conducted at MI Qur’ani Islamic Center in Jakarta. The method used in this research is field research with a qualitative descriptive approach, involving interviews, documentation, and observation. The subjects of this research are 8 classroom teachers. The results of this research show that teachers need to master four teacher competencies in developing interactive learning to achieve optimal results, create a conducive classroom environment, and make learning engaging in acquiring 21st-century 4C skills.